Free Movement of Persons and the Impelementation of EU Viza Liberalization Agreement with Albania - Hysi, Ledia (Richtmann Publishing, 2012)
The main focus of the analysis will be the migration policies within the EU, the free movement principles and restrictions thatmay be imposed to individuals by presenting an overview of the readmission policies in contemporary Europe and the effect that theybring to the field of migration, the international obligations of states and international acts to which they rely. a special attention in thispaper is paid to the analysis of the Albanian legal framework and its attitudes toward the phenomenon of migration and free movementof persons. States have the right and the duty to control migration. But in doing so they must keep reminding their citizens on why atleast some immigrants are needed and should be welcomed, and, true to Europe’s humane values, they must respect the fundamentalrights that belong to every human being, independently of their nationality, religious believe and socio-economic and culturalbackground. A specific focus in the paper will also be paid to the implementation of EU visa liberalization agreement with Albania, theissue of asylum seekers, as well as addressing the problems that serve as their motivation, aiming at the conclusion that being aEuropean citizen means being a member of a community based on full enjoyment of individual rights, as well as tolerance, mutualrespect and acceptance of diversity. It also means accepting certain obligations in respect of others, complying with the rules ofdemocracy and contributing to the development of a fair and cohesive society.